OBJECTIVES, POSSIBILITIES AND LIMITATIONS OF THE IPARD II PRORAM IN THE DEVELOPMENT OF THE AGRARIAN SECTOR OF THE REPUBLIC OF SERBIA - Prodanović, Radivoj V.; Kuzman, Boris M.; Jahić, Miralem L.; Đurić, Katarina M. (International Journal of Economic Practice and Policy, 2019)
The aim of paper is to define goals, determine possibilities and limitations for development of the agrarian sector of the Republic of Serbia using IPARD Fund. Using the historical and descriptive methods, the possibility of influencing the IPARD program on the development of agriculture in the Republic of Serbia is systematized. Also, based on the experience of other countries, potential limitations have been analyzed, which could arise when withdrawing funds from this fund. Co-financing of projects aims to increase productivity and competitiveness, harmonization with EU veterinary, sanitary and ecological standards, sustainable land management and organic production and the strengthening of infrastructure in rural areas, which is actually the biggest challenge. The degree of utilization of available resources under the IPARD program depends on several factors. Among them, institutional readiness, as well as information and education of farmers, have the greatest impact. The experiences of countries that have previously entered the process of accession to the European Union confirm the positive impact of the IPARD program on the rural economy.
Keywords: European Union; Republic of Serbia; IPARD; rural development; agriculture